A Review of Thermal Energy Storage Materials - Vimal Sagar,; Rajesh Ranjan,; Versha Joshi,; Manoj Kumar Mishra, (AG Volumes, 2022)
The goal of thermal energy storage (TES) is to make thermal energy available for later use in heating, cooling, and power production by transferring the energy from one medium to another by either heating or cooling. TES systems have widespread use in the construction and manufacturing sectors. Here, we examine TES technologies that may help increase the value of solar heat while decreasing building energy use. Storage capacity estimation and the basic concepts of numerous energy storage technologies are outlined. Storage solutions that are easy on the environment and your wallet are briefly discussed; they include water tanks, subterranean storage, and packed-bed storage. Thermo-chemical storage and latent-heat-storage systems using phase-change materials for solar space heating and cooling, heat-pump systems, solar water heating, and concentrating solar power plants are also studied. Outstanding data on the efficiency and cost of TES systems, as well as a short overview of cool thermal energy storage, are provided.